Suppressed Production of Aflatoxin B1 by Aspergillus flavus and Aspergillus parasiticus on California In-hull Almonds and Hull Fragments - Barbara Szonyi; Guangwei Huang; Tim Birmingham; Dawit Gizachew (Journal of Food Protection)
Almond hulls are economically important by-products marketed as dairy cattle feed in California. This study investigated the ability of Aspergillus flavus and Aspergillus parasiticus to grow and produce aflatoxins on almond hulls. In-hull almond kernels and hull fragments were incubated at 0.92–0.98 aw and 20–35 °C for 20 days. There was no growth and aflatoxin production at 0.92 aw by either fungus. Both A. flavus and A. parasiticus were able to grow at 0.95–0.98 aw and 20–35 °C on almond hulls. While Aspergillus flavus grew well on the in-hull almonds at 0.95–0.98 aw and 27–35 °C, it did not produce any aflatoxins under any of the study conditions. In contrast, A. parasiticus produced aflatoxins B1, G1, B2, and G2. On the in-hull kernels, A. parasiticus synthesized the highest levels of total aflatoxins (>100 µg/kg) at 27 °C and 0.95–0.98 aw. On the hull fragments, 20 °C and 0.95 aw were the ideal conditions for aflatoxin production, where the average total aflatoxin production was 35 µg/kg. The predominant aflatoxin synthesized by A. parasiticus was AFG1, accounting for up to 100% of the total aflatoxin produced on the hulls, which highlights the need to measure and report total aflatoxins (rather than AFB1 only) for almond hulls. Further studies are needed to determine the factors that limit AFB1 synthesis by A. flavus and A. parasiticus on almond hulls. Also, the types of phenolic acids present in California almond hulls need to be identified.